Analytical Study for the Determination of Norfloxacin in Pure and Pharmaceutical Formulations using Alizarin by Visible Spectrophotometric Method - okdah, Malek; kassab, kholoud (Latakia University Journal -Basic Sciences Series, 2018)
A Simple, accurate and highly sensitive spectrophotometric method have been developed for the rapid determination of Norfloxacin (NOR) in pure form and pharmaceutical formulations. The visible spectrophotometric method was based on the formation of a Red colored complex between the norfloxacin and Alizarin(AZ) at value of pH 7.15 and λmax at 508 nm. The effects of analytical parameters on the reported system were investigated. Beer’s law was obeyed in the concentration range of 6.38-95.79μg/mL, with a percentage relative standard deviation not exceed RSD= ±0.910 and the molar absorptivity coefficients was ???? =0.227×104 (L/mol.cm). Interferences of the other ingredients and excipients were not observed,limit of detection for norfloxacin was 0.67µg.ml-1 , the results showed the high accuracy and sensitivity of the developed method.